2015
DOI: 10.3201/eid2109.141841
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Effect of Human Papillomavirus Vaccines in US Population, Emerging Infections Program, 2008–2012

Abstract: Methods for surveillance of cervical precancers and associated types were developed to monitor effect of HPV vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The HPV IMPACT study collected data on CIN II–III/AIS from smaller populations, and also collected screening and vaccination data. 15 The study observed declines in HPV 16/18-attributable lesions among presumed-vaccinated young women age 18–39 between 2008 and 2012, while no significant decrease occurred in lesions among presumed-unvaccinated women. 16 National data have documented declines in vaccine-type HPV infections, as well as in anogenital warts among younger women in the United States since the introduction of the vaccine in 2006.…”
Section: Discussionmentioning
confidence: 77%
“…The HPV IMPACT study collected data on CIN II–III/AIS from smaller populations, and also collected screening and vaccination data. 15 The study observed declines in HPV 16/18-attributable lesions among presumed-vaccinated young women age 18–39 between 2008 and 2012, while no significant decrease occurred in lesions among presumed-unvaccinated women. 16 National data have documented declines in vaccine-type HPV infections, as well as in anogenital warts among younger women in the United States since the introduction of the vaccine in 2006.…”
Section: Discussionmentioning
confidence: 77%
“…Human papillomavirus genotyping is the basis for monitoring the efficacy of currently licensed prophylactic HPV vaccines, and a practical and reliable genotyping procedure is critical for establishing effective vaccine programs. The expected genotype coverages of HPV vaccines have been reported in Europe and North America . A variety of factors influence the estimation of vaccine type coverage, including the cervical disease category, clinical specimen source, genotyping method, HPV positivity, ethnicity, and correction formulae.…”
Section: Discussionmentioning
confidence: 99%
“…The expected genotype coverages of HPV vaccines have been reported in Europe and North America. (6,23,24) A variety of factors influence the estimation of vaccine type coverage, including the cervical disease category, clinical specimen source, genotyping method, HPV positivity, ethnicity, and correction formulae. Care should be taken when using DNA specimens extracted from exfoliated cervical cells to estimate HPV genotype attributions because multiple infections may be present.…”
Section: Discussionmentioning
confidence: 99%
“…12 Table 2). [58][59][60] In modified its recommendation from a three-dose schedule to a twodose schedule to be administered 6-to 12-months apart. 64 In spite of these recommendations, vaccination rates in the US have been significantly lower than those reported for other industrialized nations as well as developing countries.…”
Section: Vaccination As Prevention Strategy For Cervical Cancer Andmentioning
confidence: 99%
“…The HPV‐IMPACT pilot project was established in 2008 as a collaboration effort between the CDC and five sites in the Emerging Infections Program Network. Its objectives included monitoring the impact of HPV vaccination on CIN2+ through population‐based laboratory surveillance while collecting relevant clinical information and detailed HPV vaccination history, and estimating the annual rates of cervical cancer screening among the population in the catchment areas . HPV vaccination status in women with CIN2+ was available in 48% of patients who were age‐eligible during the analysis period.…”
Section: Introductionmentioning
confidence: 99%